Film heat-transfer coefficient for single-strength pineapple juice - Isla, Maria Theresa P. (1995)
Literature survey revealed inadequate information regarding the physical properties of pineapple juice. To provide a reference of property relationships, the experimental data on viscosity, density and heat capacity were collected. The heating of pineapple juice in a plate exchanger was studied using 22 experiments with flow rates varied between 0.63 and 22.61 lbm/s. Using the data gathered, a correlation involving appropriate dimensionless groups was developed. The correlation obtained was Nu = 80.3277 Re^0.5482Pr^-0.6461 0.075 < Re < 4.443. This will be used in predicting film coefficients during heating of single strength pineapple juice in a plate heat exchanger.